Somatic, psychological, and sexual triggers for overactive bladder syndrome in women. Issue 1 (21st February 2017) - Zilberlicht, Ariel; Haya, Nir; Feferkorn, Ido; Goldschmidt, Eyal; Kaldawy, Anis; Abramov, Yoram
Abstract : Aims: Patients with overactive bladder (OAB) often describe somatic, psychological, and sexual triggers for their symptoms. The aim of this study was to characterize these triggers and assess their impact on patients' symptoms and quality of life (QoL). Methods: Patients who visited our urogynecologic clinic between August 2015 and March 2016 and diagnosed with OAB syndrome were asked to fill a questionnaire comprising 34 statements regarding SOmatic, Psychological, and Sexual Triggers for OAB (SOPSETO). Patients additionaly completed the UDI‐6 and IIQ‐7 questionnaires. Statistical analysis was performed to determine the prevalence of each trigger and its correlation with the UDI‐6 and IIQ‐7 scores. Results: Sixty four women enrolled in this study. The SOPSETO questionnaire was found to be relaiable with Cronbach's alpha of 0.73‐0.88. Construct validity was high with good correlation between the SOPSETO and the UDI‐6 and IIQ‐7 questionnaires. The triggers which had the highest correlation with the total UDI‐6 scores were: Being far from toilets ( r  = 0.32, P  = 0.004), swimming ( r  = 0.44, P  = 0.02), taking a shower/bath ( r  = 0.36, P  = 0.004), touching water ( r  = 0.35, P  = 0.004), stepping out of a car ( r  = 0.32, P  = 0.014), and experiencing an orgasm ( r  = 0.59, P  = 0.001). The triggers: Experiencing an orgasm ( r  = 0.4, P  = 0.033), having intercourse ( r  = 0.53, P  = 0.002), stepping out of a car ( r  = 0.45, P  = 0.001), and touching water ( r  = 0.28, P  = 0.03) most significantly correlated with the total IIQ‐7 scores. Conclusions: Certain somatic, psychological, and sexual factors may trigger OAB symptoms and are therefore potential targets for behavioral therapy of this disorder, and for further research regarding its pathophysiological mechanisms.